2009
DOI: 10.1101/gad.524209
|View full text |Cite
|
Sign up to set email alerts
|

The SESA network links duplication of the yeast centrosome with the protein translation machinery

Abstract: The yeast spindle pole body (SPB), the functional equivalent of mammalian centrosome, duplicates in G1/S phase of the cell cycle and then becomes inserted into the nuclear envelope. Here we describe a link between SPB duplication and targeted translation control. When insertion of the newly formed SPB into the nuclear envelope fails, the SESA network comprising the GYF domain protein Smy2, the translation inhibitor Eap1, the mRNAbinding protein Scp160 and the Asc1 protein, specifically inhibits initiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 68 publications
10
135
0
Order By: Relevance
“…For example, the expression of STE12, GPA2, and CLN1 was shown to be translationally upregulated in caf20D cells during filamentous growth, and STE12 regulation was dependent on Caf20 (Park et al 2006b). Eap1 (together with Scp160, Asc1, and Smy2) is involved in translational repression of the POM34 mRNA (Sezen et al 2009). These data support the idea that the 4E-BPs can interact with and repress the translation of particular mRNA targets, possibly via interactions with other sequencespecific mRNA binding proteins, similar to examples from higher eukaryotes (Kong and Lasko 2012).…”
Section: Regulating Eif4e-eif4g Interactions By 4e-bpsmentioning
confidence: 99%
“…For example, the expression of STE12, GPA2, and CLN1 was shown to be translationally upregulated in caf20D cells during filamentous growth, and STE12 regulation was dependent on Caf20 (Park et al 2006b). Eap1 (together with Scp160, Asc1, and Smy2) is involved in translational repression of the POM34 mRNA (Sezen et al 2009). These data support the idea that the 4E-BPs can interact with and repress the translation of particular mRNA targets, possibly via interactions with other sequencespecific mRNA binding proteins, similar to examples from higher eukaryotes (Kong and Lasko 2012).…”
Section: Regulating Eif4e-eif4g Interactions By 4e-bpsmentioning
confidence: 99%
“…The C. elegans genome contains three additional genes that encode well-conserved GYF domains, but none show any sequence similarity with SAO-1 outside of the GYF domain (Kofler and Freund 2006). In yeast, GYFdomain proteins have been associated with a variety of cellular functions, such as COPII vesicle formation (Higashio et al 2008), membrane traffic (Georgiev et al 2008), genespecific inhibition of translation initiation (Sezen et al 2009), and mRNA splicing (Bialkowska and Kurlandzka 2002). Identification of binding partners for human GYF domains also supports involvement in vesicle transport and mRNA processing (Kofler et al 2009;Ash et al 2010).…”
Section: Genotype Of Mothermentioning
confidence: 99%
“…Specific nucleoporin deletions suppress the growth defects of mps3 mutants: It was previously reported that deletion of genes coding for the POM nucleoporins Pom152p or Pom34p can rescue defects seen in certain mutants that disrupt SPB insertion, including ndc1, bbp1, and mps2 mutants (Chial et al 1998;Sezen et al 2009). To test whether POM gene deletions could also relieve defects associated with MPS3 mutation, POM152 and POM34 were individually deleted in haploid strains containing either wild-type MPS3 or mps3-1 alleles.…”
Section: Spb Mutant Allelementioning
confidence: 99%
“…Moreover, while there is considerable overlap between the nucleoporin deletions that suppress mps2D and mps3-1, the spectrum of suppressing mutants is not identical: nup188D could partially suppress mps3-1 but not mps2D (Sezen et al 2009), and nup157D suppressed mps3-1 but not mps2-1 (see below).…”
Section: Spb Mutant Allelementioning
confidence: 99%
See 1 more Smart Citation